Incidence and Clinical Predictors of Ocular Candidiasis in Patients with Candida Fungemia - Khalid, Ayesha; Clough, Lisa A.; Symons, R. C. Andrew; Mahnken, Jonathan D.; Dong, Lei; Eid, Albert J. (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Purpose. The aim of this study is to determine the incidence and the predictors of ocular candidiasis among patient with Candida fungemia. Methods. We retrospectively reviewed the charts of all patients diagnosed with candidemia at the University of Kansas Medical Center during February 2000–March 2010. Data regarding patients’ demographics, clinical characteristics, laboratory results, and ophthalmology examination findings were collected. Results. A total of 283 patients with candidemia were enrolled. The mean age (± standard deviation) was 55 ± 18 years; 66% were male. The most commonly isolated Candida species were C. albicans (54%), C. parapsilosis (20%), C. glabrata (13%), and C. tropicalis (8%). Only 144 (51%) patients were evaluated by ophthalmology; however, the proportion of patients who were formally evaluated by an ophthalmologist increased during the study period (9%in 2000 up to 73%in 2010; P<0.0001). Evidence of ocular candidiasis was present in 18 (12.5%) patients. Visual symptoms were reported by 5 of 18 (28%) patients. In multivariable analysis, no predictors of ocular candidiasis were identified. Conclusions. The incidence of ocular candidiasis among patients with fungemia remains elevated. Most patients are asymptomatic and therefore all patients with candidemia should undergo fundoscopic examination to rule out ocular involvement.